Application of Restorative Justice Principles in Judges' Considerations in Decisions to Release from All Legal Charges (Decision Case Study Number: 28/Pid.B/2022/PN.LBB) - Permana, Yondra; Yoserwan, Yoserwan; Elvandari, Siska (UNES Law Review, 2024)
This research aims to examine and analyze the application of the principles of restorative justice to judges' considerations in decisions to release all legal claims (case study decision number:28/Pid.B/2022/PN.LBB). This research uses the method normative juridical, while the approach used in this research is a statutory approach , then the data is analyzed using qualitative descriptive research analysis methods. The results of this research are : 1) Application of restorative justice in Decision No.28/Pid.B/2022/PN.Lbb, where the judge handed down a decision to release all legal charges against Defendant Dedi on charges of theft. 2) In terms of implementing the principles of Restorative Justice This is an obstacle to the implementation of restorative justice, including in very serious violations, the difficulty in creating public trust in the implementation of restorative justice in serious cases. Apart from that, the reasons for recidivist actions by perpetrators after undergoing a restorative justice process raise questions from the public if they have to repeat the process several times against the same perpetrator.